Evaluating the Effectiveness of Bibliotherapy on Self-Compassion and Shame in Individuals with Eating Disorders - Lee, Angel; Iskandar, Amirul (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to evaluate the effectiveness of a bibliotherapy intervention on enhancing self-compassion and reducing shame in individuals with eating disorders. Methods and Materials: The study employed a randomized controlled trial design involving 30 participants with clinically diagnosed eating disorders from Malaysia, randomly assigned to either an intervention group (n = 15) receiving a six-session bibliotherapy program or a control group (n = 15) receiving no intervention. The bibliotherapy sessions were conducted weekly over six weeks, incorporating evidence-based reading materials and reflective exercises targeting self-compassion and shame. Standardized instruments—the Self-Compassion Scale (SCS) and the Experience of Shame Scale (ESS)—were administered at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests via SPSS-27. Findings: Descriptive analysis indicated that the intervention group experienced an increase in self-compassion from pre-test (M = 2.61, SD = 0.33) to post-test (M = 3.39, SD = 0.41) and follow-up (M = 3.31, SD = 0.38), while shame scores decreased from pre-test (M = 3.47, SD = 0.29) to post-test (M = 2.68, SD = 0.33) and follow-up (M = 2.72, SD = 0.35). The control group showed no significant changes. Repeated measures ANOVA revealed significant time × group interaction effects for both self-compassion (F(2, 56) = 20.31, p < .001, η² = .43) and shame (F(2, 56) = 17.82, p < .001, η² = .39). Bonferroni post-hoc comparisons confirmed that changes from pre-test to post-test and follow-up were statistically significant for the intervention group (p < .001), but not between post-test and follow-up (p > .05), indicating sustained effects. Conclusion: The findings suggest that bibliotherapy is an effective and durable intervention for increasing self-compassion and reducing shame in individuals with eating disorders.